ANALISIS FAKTOR YANG MEMPENGARUHI PRICE EARNING RATIO SEBAGAI DASAR PENILAIAN SAHAM - Crystha Armereo (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
The purpose of research is to test and analyze the factors influence Price Earning Ratio as basic of stock appraisal on manufacture companies listed in Indonesia Stock Exchange of from 2009-2013. This research is descriptive research with quantitative approach. Method of collecting data uses documentation is secondary data were sourced from Capital Market Directory in 2009-2013and data were sourced from Indonesia Stock Echange Company Report in year 2013. Method of data analysis uses Factor Analysis, especially EFA(Explanatory Factor Analysis) through method of PCA (Principal Component Analysis). Results of the research showed that (1) factor of capitals and debts with percentage35.297%, it means this factor is dominant factor can explain 35.297%of the variables’ variance; (2) factor of dividends and shares with percentage 30.293%, it means this factor can explain 30.293% of the variables’ variance; (3) factor of benefits level with percentage 21.254%, it means this factor can explain 21.254% of the variables’ variance; (4) factor of sales level with percentage 6.747%, it means this factor can explain 6.392% of the variables’ varianceand (5) other factors with percentage 6.747%, it means this factor can explain 6.392%of the variables’ variance. Keywords: Factor Analysis;Price Earning Ratio;Manufacture Companies; Indonesia Stock Exchange